Semiotic Community Perspectives on Offerings in Traditional Jathilan Performances in Yogyakarta: A Semiotic Study - Piri, Tirza Benedicta; Avero Pramasheilla, Dinda Assalia; Gustyawan, Tofan; Irianto, Ikhsan Satria (Creativity And Research Theatre Journal, 2024)
In Javanese terms, Jathilan stands for "Jarane jan thil-thilan" which means "The horse moves irregularly". People in the city of Yogyakarta know jathilan as part of a certain ritual procession that uses the properties of an artificial horse or commonly called jaran kepang. Jathilan traditional art itself cannot be separated from rituals and sesaji used as a form of expression of prayer and hope. The formulation of the problem in this journal is: How do people view the belief that sesaji are a "culture" that will continue to live side by side with humans?. Using qualitative data analysis, this study examined the symbolic meaning of offerings in Yogyakarta's traditional art ceremony of jathilan. Offerings are a manifestation of moral values, reverence for ancestors, and the existence of a healthy interaction between humans and nature, according to the study's findings from the community perspective.